TREATMENT CHARACTERISTICS OF ACUTE CORONARY SYNDROME IN ELDERLY PATIENTS: PRACTICE OF N.I. PIROGOV CITY CLINICAL HOSPITAL №1 - M. Yu. Gilyarov; M. O. Zheltoukhova; E. V. Konstantinova; M. D. Muksinova; L. S. Muradova; A. P. Nesterov; A. E. Udovichenko (Рациональная фармакотерапия в кардиологии)
Aim. Assessment of compliance the management of elderly patients (≥75 years) with acute coronary syndrome (ACS) with existing guidelines and evaluation of ACS features during the last two years of working period of the Regional vascular center and compare the results with the data from Russian and foreign registries, randomized clinical studies (RCS) and recommendations. Material and methods. Analysis of diagnostic and treatment data of 999 patients, aged 75 years and over, who were taken by ambulance or made their own way to N. I. Pirogov City Clinical Hospital №1 (CCH №1) in Moscow and were hospitalized during the period between the 1st January 2014 and the 31st of December 2015 in the intensive care unit for patients with myocardial infarction with the initial diagnoses of ACS, myocardial infarction and unstable angina. Results. The elderly patients with ACS admitted to the CCH №1 in 2014 and 2015 were 41% and 54% of all patients with ACS, respectively; women prevailed in all age subgroups. There was no age difference between the subgroups of ACS in patients with elevation ST-segment and ACS in patients without ST-segment elevation. A high frequency of comorbidity in the elderly patients with ACS was observed; hypertension was the most common disease with an incidence rate of 95% without significant difference between the genders. The incidence of percutaneous coronary intervention (PCI) and coronary angiography (CAG) significantly increased in 2015 compared with 2014 (p<0.0001, risk ratio 0.56, 95% confidence interval 0.420.76). A reduction in hospital deaths was also found (p<0.0001, risk ratio 1.51, 95% confidence interval 0.94-2.43). Dual antiplatelet therapy (DAT) was prescribed to elderly patients in clinical practice approximately in 70% of cases; DAT was performed significantly more often in 2015 than in 2014. Conclusion. There are a high percentage of the elderly patients with ACS admitted to the CCH №1. This proportion is dramatically higher than this in the Russian and foreign registries and RCS, that could influence on the outcome of patient care. The widespread use of interventional diagnostic and treatment methods (CAG and PCI) allows to improve substantially the clinical outcomes of ACS. A possibility of unconditional following the guidelines regarding the prescription of DAT to the elderly patients with ACS in real clinical practice may be limited by the high incidence of concomitant pathology.